Current Research in Embryology 2011
DOI: 10.1201/b12877-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diabetes Alters Transcriptional Programs in the Developing Embryo

Abstract: Background: Heat shock proteins (Hsps) are a set of highly conserved proteins, Hsp105, has been suggested to play a role in reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Yuan et al () observed that expression of Hsp105 was mainly in the luminal epithelium on day 1 of pregnancy, and reached a peak level on day 5, whereas in stroma cells, adjacent to the implanting embryo, the strongest expression of Hsp105 was observed on day 6. It was speculated that temporal and spatial changes in Hsp105 expression in pregnant rat uterus may play a physiological role in regulating embryo implantation (Yuan et al, ). In this study, we observed that Hsp70 mainly distributed in decidual‐stromal cells on day 3 of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al () observed that expression of Hsp105 was mainly in the luminal epithelium on day 1 of pregnancy, and reached a peak level on day 5, whereas in stroma cells, adjacent to the implanting embryo, the strongest expression of Hsp105 was observed on day 6. It was speculated that temporal and spatial changes in Hsp105 expression in pregnant rat uterus may play a physiological role in regulating embryo implantation (Yuan et al, ). In this study, we observed that Hsp70 mainly distributed in decidual‐stromal cells on day 3 of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression IK cytokine protein in pseudopregnant mouse endometrium was markedly lower than that in normal pregnant status and no peak level was observed during the whole pseudopregnant period. It was known that oligodeoxynucleotide can be effectively absorbed by the uterine luminal and glandular epithelium and stroma cells (23). Antisense oligodeoxynucleotide is known to have a half life of 24-48 h in certain tissues (24).…”
Section: Discussionmentioning
confidence: 99%
“…Once embryos attach on the uterus, endometrial stromal cells initiate specialized transformation named decidualization, accompanying the angiogenesis and inflammatory responses [3,4]. Many heat shock proteins (HSP) are evoked during decidualization, including small heat shock protein family [5–8].…”
Section: Introductionmentioning
confidence: 99%